Konsep Taghut Menurut Pemikiran Sayyid Qutb (Telaah Tafsir Fi Zilal al-Qur'an) - Albani, Albani; , Dr. Sudarno Shobron, M.Ag; , Dr. Muinudinillah Basri, M.A (2015)
Sayyid Quthb was one of Islamic movement leaders in the twentieth century who often claimed to be an icon of Islamic fundamentalist movement. His sharp thoughts in his works which often criticizes Western civilization make many consider him as an Islamic radicalism pioneer and contributor of strict understanding that ignite worldwide terrorism actions. His works such as Ma'âlim fi ath-Tharîq and Fî Zhilâl al-Qur'ân have been considered very dangerous and used as excuses in the court that delivered him to the death sentence from Egyptian government at that time. This study is a library research using a theological approach and intended to examine Sayyid Quthb's thought of concept of thâghût, which he put forward while interpreting al-Qur'an verses talking about thâghût in his great work; Tafsir Fî Zhilâl al-Qur'ân. This study will also examine the relevance of Sayyid Quthb's interpretation of thâghût in the present context. Source of data used in this study is Sayyid Quthb's book Fî Zhilâl al-Qur'ân as the primary data, especially his interpretation of verses about thâghût in Al-Qur'an. Works of others related to Sayyid Quthb's thought and books that discuss thâghût are studied as secondary data to strengthen the argument built in this thesis. Once collected using documentary method, these data then are processed using content analysis method. Based on the study results, interpretation of thâghût meaning expressed by Sayyid Quthb is more extent when compared to interpretations by previous interpreters. However, Sayyid Quthb's interpretation generally is not in contradiction to other interpreters' opinion. Sayyid Quthb interprets thâghût in haraki (movement) context, especially when interpreting the meaning of thâghût in Madaniyah verses. This is influenced by his mainstream thought as a movement leader who has a strong belief in Islamic ideology and rejects values outside Islam. The concept of thâghût according to Sayyid Quthb's thought has strategic relevance to monotheistic call enforcement, agenda of power Islamization, enforcement of Islamic law prospects in Indonesia, relevance to the extending of thâghût meaning in the present dynamic era which may brings out more various and complex thâghût, and relevance to the problems of people today about the attitude is considered pagan fellow muslims (takfiri). Keywords : Concept of Thâghût, Sayyid Quthb, Fî Zhilâl al-Qur'ân.